Peningkatan Hasil Belajar Matematika Melalui Model Pembelajaran Cooperative Learning Tipe Teams Games Tournament (TGT) pada Siswa Kelas IV di SDN 01 Winongo - Andin Badiatus Sholikhah; Bambang Eko Hari Cahyono; Ike Yusda Andriani (Pusat Riset dan Inovasi Nasional, 2025)
Teams Games Tournament (TGT) is a cooperative learning model that helps fourth-grade students at SDN 01 Winongo do better in math. The goal of this project is to show how the TGT cooperative learning model can help students learn math better and explain how it does so. A study of how well students learned math before and after the instruction was used to get the data analysis. In this study, the assistance was supposed to lead to each student getting a final percentage score of at least 70%. The results of this study showed that before the help, kids had an average score of 57 on tests related to math. In Cycle I, students learned math on average to a level of 70, but by Cycle II, they were at a level of 90. With this information, we can say that using the TGT learning model helps kids get better at math. All of the people who took part in the final review got the effects that were expected from the intervention.